Effect of acute experimental hand pain on left–right discrimination response latency for hand recognition. (1st November 2020) - Phillips, Nichole; Hach, Sylvia; Mannion, Jamie; Moran, Robert
ABSTRACT: Background : Recent work has indicated that acute experimental pain affects left–right discrimination latency. This phenomenon highlights an effect of pain on the cortex that may have significant clinical importance in the form of pain state assessment. However, to date only limited study has further qualified this effect. A more thorough understanding of the magnitude and characteristics of this phenomenon is needed to determine its potential clinical utility. Objective : This study aimed to closely replicate previous studies investigating response latency changes for left–right discrimination judgements as a result of acute experimental pain. Methods : Twenty-two right-handed participants ( n = 11 female, n = 11 male) free from pain, analgesia use, pain-related conditions, upper limb trauma/conditions, visual impairment, and dyslexia took part in this study. Participants completed a hand left–right discrimination judgement task before, during, and after an experimental pain stimulus was delivered to each hand separately. Experimental pain was achieved using an intramuscular injection of hypertonic (5%) saline into the thenar eminence of the left and right hands. Mean response times for the left–right discrimination task were determined and compared for pain location (right, left), pain condition (before, during, after), and image laterality (right, left). Pain intensity was rated at 20 s intervals during each left–right discrimination task. Results : A main effect of pain condition ( p = 0.028) confirmed that pain intensity was significantly higher in the "during pain" condition compared to the "before pain" and "after pain" conditions. A main effect of image laterality ( p = 0.002) further showed that response latency for right-hand pain was significantly shorter compared to left-hand pain. No significant interaction between the factors pain location and image laterality ( p = 0.086) was found. For right-hand pain, response latencies for the unaffected hand were, however, descriptively greater compared to the affected hand, and this was not the case for left-hand pain. Furthermore, no main effect of pain stimulus or of pain location on response times was found ( p = 1.00 and p = 0.202, respectively). Conclusion : Our results were not consistent with previous hand left–right discrimination response latency results and may cast doubt on the attentional bias hypothesis that is currently considered to underpin response latency changes during acute experimental hand pain. Individual responses to pain, subsets of participants, and differing mental rotation strategies during the left–right discrimination task may have influenced the results.